Pengaruh Program Diskon Terhadap Keputusan Pembelian Konsumen pada Alfamart Cabang Panda Kabupaten Bima - Khofifah Indar Parawansyah; Muhajirin Muhajirin; Irma Mardian (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
This study aims to analyze the influence of discount programs on consumer purchase decisions at Alfamart Panda Branch, Bima Regency. The research method used is quantitative with data collection through questionnaires distributed to Alfamart consumers. The results of the study show that discount programs have a significant influence on consumer purchase decisions. The discounts offered by Alfamart have managed to attract consumers' attention and increase the intensity of purchases. These findings have practical implications for retail managers in designing effective marketing strategies to increase sales.